Who is the "reasonable investor"?. Issue 4 (7th November 2016) - Tuttle, Jonathan R.; Kaplan, Matthew E.; Pedersen, Benjamin R.
Abstract : Purpose: To discuss how two recent court decisions applied the materiality standard concerning information disclosed to investors and the definition of a "reasonable investor". Design/methodology/approach: Explains the origins and evolution of the materiality standard and the "reasonable investor" paradigm, discusses the difficulty in applying the materiality standard in the absence of a clear definition of the "reasonable investor", and addresses potential implications of two 2016 cases, Flannery v. SEC and United States v. Litvak, on whether materiality should be applied on a subjective, rather than objective, basis and evidentiary burdens in proving materiality. Findings: Flannery and Litvak suggest that, in assessing what information is material to a "reasonable investor", courts may place increasing weight on the relative sophistication of investors, the types of securities and the nature of the markets in which they are investing, and types of information investors in those securities and markets typically consider to be material. Originality/value: Informed analysis by experienced practitioners in capital markets, financial services and securities litigation.